Development of the IIUM hybrid airship - Ping, Julian T.K.; Andan, Amelda D.; Asrar, Waqar; Omar, Ashraf Ali (2010)
Hybrid airship is an unconventional type of airship being developed since a few decades ago and is now being tried on a significant scale. In this paper, the preliminary design steps of a winged hull hybrid airship will be outlined and discussed together with a way to achieve controllability of the hybrid airship during both STOL (Short take off and Landing) and cruising mode as well as its aerodynamic characteristics.